Efficacy of multidisciplinary treatment for patients with chronic low back pain: a prospective clinical study in 395 patients - Moradi, Babak; Hagmann, Sébastien; Zahlten-Hinguranage, Anita; Caldeira, Fernanda; Putz, Cornelia; Rosshirt, Nils; Schönit, Eva; Mesrian, Alireza; Schiltenwolf, Marcus; Neubauer, Eva (Journal of clinical rheumatology, 2012)
BACKGROUND: The effectiveness of multidisciplinary treatment programs varies throughout the literature, and it remains controversial how therapy outcome is affected by patients' individual parameters and which treatment settings work best. OBJECTIVES: We set out to examine the impact of patient variables on the effectiveness of a 3-week multidisciplinary treatment program in patients with chronic low back pain. By presenting effect sizes, we aimed to enable the comparison of our findings with other studies across disciplines. METHODS: Data on 395 patients were prospectively collected at study entry, at the end of the program (T1) and after 6 months' follow-up (T2). Relevant therapy outcomes were analyzed by presenting effect sizes with Cohen's d. Group comparisons were performed for sociodemographic and clinical features to determine the impact on therapy outcome. RESULTS: Medium effect sizes (d = -0.6 to -0.7) were shown for visual analog scale (VAS) after treatment and at T2, indicating clinically relevant pain relief. Significant changes in pain-related disability were observed immediately at T1 with a strong treatment effect (d = 0.8). Functional capacity was improved with low to medium effect sizes (0.4-0.5). Quality-of-life subscales (36-item Short Form Health Survey) improved significantly at T1 for physical function, vitality, and mental health (d = 0.5-0.8). Center for Epidemiological Studies - Depression Scale scores improved significantly with strong effect sizes of d = 0.7. Sociodemographic parameters displayed a significant impact on effect sizes for visual analog scale at T2, with females (d = -0.9), age group 30 to 39 years (d = -1), and patients with low physical job exposure (d = -0.9) benefiting most. An increase in number of pain locations (-0.7) and severity of accompanying pain (-0.7) in other body areas significantly impaired therapy outcome and effect sizes of VAS. CONCLUSIONS: Thus, multidisciplinary treatment ameliorates pain, functional restoration, and quality of life with medium to high effect sizes even for patients with a long history of chronic back pain. Effect sizes are higher than for monodisciplinary treatments and treatment effects remained stable at 6-month follow-up in a longitudinal uncontrolled study design. Thus, we believe that multidisciplinary treatment is vital for the treatment of patients with chronic low back pain. The impact of sociodemographic and pain-related parameters needs to be taken into account when including patients in an appropriate treatment program. We emphasize the presentation of effect sizes as a vital treatment evaluation to enable cross-sectional comparison of therapy outcomes.
Gesehen am 03.05.2012